Honey Bee Colony Health Challenges and Sustainable Solutions - Sammataro, Diana; Yoder, Jay A. (Taylor & Francis, 2012)
This book summarizes the current progress of bee researchers investigating the status of honey bees and possible reasons for their decline, providing a basis for establishing management methods that maintain colony health. Integrating discussion of Colony Collapse Disorder, the chapters provide information on the new microsporidian Nosema ceranae pathogens, the current status of the parasitic bee mites, updates on bee viruses, and the effects these problems are having on our important bee pollinators. The text also presents methods for diagnosing diseases and includes color illustrations and tables.